PENERAPAN PRINSIP FAIR-TRADE DALAM UPAYA PENINGKATAN KESEJAHTERAAN PETANI KOPI DI JAWA BARAT - Nasution, Ryan Harris (Dialogia Iuridica, 2019)
Indonesia is currently one of the largest coffee exporters country in the world. Coffee from Indonesia often scores highest in various international coffee auctions. Along with the development of the Indonesian coffee industry, it is expected to improve the lives of farmers as well. But in the end there were still many coffee farmers whose lives were less prosperous. There are problems experienced by farmers and countries that help provide protection. On this basis the Republic Indonesia Government made Law Number 19 of 2013 concerning Protection and Empowerment of Farmers who are expected to overcome various problems experienced by farmers. This study aims to find and discuss fair trade conditions in laws in Jawa Barat (Indonesia), especially for coffee farmers so that they can improve the welfare of farmers. The study also found findings and discussions about laws related to improving the welfare of coffee farmers in Indonesia. This research is expected to provide practical and practical uses, namely those that can be used in the development of agricultural law and provide criticism and suggestions for making laws on agriculture that specifically achieve the independence and welfare of coffee farmers. This research is also expected to inform a public about fair trade, both the owners of coffee outlets, coffee roaster and coffee farmers as the main producers.